2015
DOI: 10.1111/hsc.12224
|View full text |Cite
|
Sign up to set email alerts
|

Long-term care use among old people in their last 2 years of life: variations across Finland

Abstract: Variations across Finland in the use of six different long-term care (LTC) services among old people in their last 2 years of life, and the effects of characteristics of municipalities on the variations were studied. We studied variations in the use of residential home, sheltered housing, regular home care and inpatient care in health centre wards by using national registers. We studied how the use of LTC was associated with characteristics of the individuals and in particular characteristics of the municipali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…More affluent regions or municipalities may provide more services (i.e., have lower eligibility thresholds) or be able to attract more providers and this postal code lottery may be exacerbated by older people’s limitations to travel or relocate. On this matter, available empirical findings suggest plenty of geographical variation across countries [ 30 , 31 , 32 , 33 , 34 ], but these seem to be small and closely associated with geographical distribution of need and may not therefore reflect inequity.…”
Section: Introductionmentioning
confidence: 99%
“…More affluent regions or municipalities may provide more services (i.e., have lower eligibility thresholds) or be able to attract more providers and this postal code lottery may be exacerbated by older people’s limitations to travel or relocate. On this matter, available empirical findings suggest plenty of geographical variation across countries [ 30 , 31 , 32 , 33 , 34 ], but these seem to be small and closely associated with geographical distribution of need and may not therefore reflect inequity.…”
Section: Introductionmentioning
confidence: 99%
“…In Finland, we know that the distribution of health and social welfare services and access to services are relatively good at the macro level (Pulkki et al, 2015;Vaarama et al, 2014;Valkonen et al, 2014). Even though most clients feel that the accessibility of social services is at a good level, some clients repeatedly reported that client payments were too expensive, services could not be accessed quickly enough, or there were other difficulties with the accessibility of services (Ilmarinen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Upper non-manuals were more frequently in privately provided LTC facilities than other groups. It is known that the care delivery system characteristics, the availability of LTC by different providers, affect the use of LTC services in Finland (Pulkki et al 2016). Participants in this study, however, reside in the same municipality, where service provision is the same for all inhabitants.…”
Section: Discussionmentioning
confidence: 99%